Pemberdayaan IRT Aisyiah dengan Mesin Pengaduk dan Pemotong Rumput Laut - Muntasir Muntasir; Muhajirin Dean; Mozart Harpian Fereal Mori Uma; Septania Rahmawati Ruth Taneo; Tanty Rahayu (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: To improve production efficiency and quality of dodol (sweet potato cracker), crackers, and seaweed sticks at the IRT Aisyiah Alak Kupang household through the adoption of innovative mixers and cutting machines. Methodology/Approach: The study was conducted at the IRT Aisyiah Alak Kupang with mixers and cutting machines sourced from Maksindo Surabaya. Methods included field surveys, machine operation training, technical assistance, and production evaluation. Data were analyzed quantitatively and qualitatively using simple production analysis software and the participatory rural appraisal approach. Results/Findings: Dodol production capacity increased from 3 kg to 6 kg per week, and crackers and seaweed sticks from 2 kg to 4 kg per week, respectively. Production time decreased by about 50%, partner income doubled, and marketing reach expanded through digital platforms and branding development. Conclusions: The community empowerment program at IRT Aisyiah Alak Kupang successfully enhanced efficiency, capacity, and quality of dodol and seaweed sticks. The implementation of mixing and cutting machines, together with digital marketing, improved partner income and business sustainability. Ongoing mentoring is provided, and the development of supporting equipment, such as modern drying tools, is recommended for further study to strengthen program outcomes. Limitations: Testing was limited to a single partner location and did not extensively explore various machine types or digital marketing techniques. Contributions: The study contributes to the development of appropriate technology for local food processing, particularly in the seaweed industry of East Nusa Tenggara, and strengthens community economic empowerment while preserving local wisdom.